Polymorphonuclear Leukocyte Transendothelial Migration Proceeds at Blood-Brain Barrier in Neonatal Meningitis - Niu, Zhuo; Chen, Yu-Hua; Zhang, Ke (Frontiers in Microbiology, 2020)
Neonatal bacterial meningitis remains a life-threatening and causative sequelae disease in newborns, despite the effective usage of antibiotics and improved critical medical care. Polymorphonuclear leukocyte (PMN) transendothelial migration across the blood-brain barrier (BBB), one of the three hallmarks of bacterial meningitis, now is considered as a “double-edge sword”. When participating in host immune system defensing against virulent pathogens, it results in tissue inflammation and following severe damage of central nervous system (CNS) at the same time, which contributes to a disastrous consequence. Recently, several researches have focused on this multi-step process and the mechanism of how the virulent factors of different pathogens influence PMN migration. The great progression they made has enlightened a new research hotspot and a novel therapeutic strategy. This mini review outlines the determinants and progression of PMN transmigration in neonatal meningitis caused by different predominant pathogens.